DEVELOPMENT AND PERSPECTIVES OF THE STATE BORDER GUARD E-LEARNING SYSTEM - Pavlovičs, Jans (Border Security and Management, 2018)
In this article, the author focuses on the development of e-learning in the State Border Guard of the Republic of Latvia. The author gives an idea of the world trends in the development of e-learning, the features and possibilities of using it in the State Border Guard of the Republic of Latvia. Author indicates possible options for the development of e-learning, as well as difficulties and possible solutions. This research is lengthy and implies further research of the use of e-learning in the State Border Guard of the Republic of Latvia.